Democracy and the next American economy : where prosperity meets justice - Ramos, Henry A. J., 1959- (Arte Publico Press, 2019)
This informative nonfiction work offers a critique of current trends in American political economy, calls for organized action and provides a road map for the future based on successfully implemented strategies that support equity in society, restore democratic processes, implement better urban planning and protect the environment.